Chloride Uptake by Brush Border Membrane Vesicles Isolated from Rabbit Renal Cortex: COUPLING TO PROTON GRADIENTS AND K+ DIFFUSION POTENTIALS - David G. Warnock; Victoria J. Yee (The Journal of Clinical Investigation, 1981)
Brush border membrane vesicles were isolated from rabbit renal cortex by Mg++-precipitation and differential centrifugation. 36Cl− and [3H]glucose uptakes were simultaneously determined by a rapid filtration technique. Lysis of the vesicles with distilled water abolished 90-95% of the radioactivity on the filters, suggesting that nearly all of the 36Cl− and [3H]glucose counts represented uptake into an osmotically reactive intravesicular space. Inwardly directed K+ gradients plus valinomycin stimulated 36Cl− uptake, demonstrating a conductive pathway for chloride uptake into brush-border membrane vesicles. 36Cl− uptake could also be stimulated by inwardly directed proton gradients (pHoutside < pHinside). This effect was seen in the absence of sodium, as well as in the presence of valinomycin when the vesicles had equal K+ concentrations inside and out. An “overshoot” phenomenon was observed when external 36Cl− was 2 mM and the external pH was lowered from 7.5 to 6.0 or to 4.5. The effect of the proton gradient was presumed to be different from the conductive mechanism because (a) the stimulation of 36Cl− uptake by inwardly directed K+ diffusion potentials was additive to the proton gradient effect, and (b) competition studies revealed statistically significant effects of thiocyanate on the conductive pathway, but not on the proton-driven pathway. HCl cotransport or anion exchange are electrically neutral mechanisms which could couple 36Cl− uptake to inwardly-directed proton gradients in a brush border membrane vesicle. If both electrically neutral and conductive path ways for chloride transport are present in the luminal membrane of the proximal tubule, then the mechanism as well as the direction of net chloride transport will be influenced by the nature of the accompanying cation transport process.